2021
DOI: 10.1108/mf-03-2020-0143
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and bank performance in Vietnam

Abstract: PurposeFor the past two decades, intellectual capital has played an increasingly important role in firm performance around the world. However, the importance of intellectual capital in Vietnam, and especially in the banking sector, has largely been ignored in the literature. This study is the first to examine the effect of intellectual capital on bank performance in Vietnam. In this paper, intellectual capital is decomposed into three components: (1) capital employed efficiency, (2) human capital efficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 51 publications
3
31
2
1
Order By: Relevance
“…(2) Independent Variables. is study uses Pulic [17]'s VAIC model to measure IC efficiency of listed banks, consistent with Meles et al [34], Tran and Vo [36], Xu et al [38], Mondal and Ghosh [41], Vo and Tran [43], Ousama et al [62], and Le and Nguyen [63]. e VAIC model identifies banks with profitability in maximizing their economic performance in the process of value creation.…”
Section: Variablesmentioning
confidence: 73%
See 1 more Smart Citation
“…(2) Independent Variables. is study uses Pulic [17]'s VAIC model to measure IC efficiency of listed banks, consistent with Meles et al [34], Tran and Vo [36], Xu et al [38], Mondal and Ghosh [41], Vo and Tran [43], Ousama et al [62], and Le and Nguyen [63]. e VAIC model identifies banks with profitability in maximizing their economic performance in the process of value creation.…”
Section: Variablesmentioning
confidence: 73%
“…Joshi et al [42] found that Australian bank performance is highly influenced by HC, while physical and structural capitals play a minor role in value creation. e findings of Vo and Tran [43] showed that the performance of listed banks in Vietnam is driven primarily by physical capital.…”
Section: Ic and Bank Performancementioning
confidence: 99%
“…Nonaka et al (2017) argue that companies need to create new knowledge to ensure their future existence, so they must have good strategic and resource management. Several previous studies analyse the IC components independently of their dependent variables, such as research (Akkas and Asutay 2022;Chatterjee et al 2022;Dalwai and Mohammadi 2020;Dalwai and Salehi 2021;Kweh et al 2021;Vo and Tran 2021). This opinion considers each component's specific impact on performance rather than the impact of IC more broadly.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Nawaz and Haniffa (2017) find that SC is not significant to performance. Tiwari and Vidyarthi (2018) find evidence that CE is not significant for performance, while Vo and Tran (2021) find that only CE is proven to affect performance.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation